Fruit quality of South African cactus pear cultivars - Rothman, Anna Maria Petronella (University of the Free State, 2010)
The cultivation of cactus pears requires low input and it has been grown widely in drier areas of South-Africa as fodder crop, particularly for times of serious drought. Cactus pears also serve as a source of inexpensive nutritious food for lower income groups Sugar is the main determent of taste of the cactus pear cultivar and content value range from 10 °Brix to 17 °Brix. Glucose is the predominant sugar with fructose as the second sugar, thus the fruit pulp is very sweet. The pulp of the cactus pear cultivar consists of a high pH value (> 4.5) and low acidity level (0.03-0.12 % ), (SaenzHernandez, 1985; Brutch, 1993; Piga, 2004; Salim, 2009). The aim of this study was to determine the fruit quality of cactus pear fruit. Physical/chemical and sensory quality attributes were evaluated for two agricultural seasons ( 2007 and 2008). The influence of factors such as rainfall and temperature on quality was determined. Furthermore, sensory analysis was used to distinguish among the available 33 cultivars, not only for their taste, but also to establish the cultivar most stable to varying environmental conditions. This study determined whether sensory quality of cactus pear fruit was influenced by the physical/chemical parameters by correlating the physical/chemical data with the sensory analysis. There were highly significant differences observed in terms of physical/chemical composition (p < 0.001) among 33 different cactus pear cultivars in South Africa, for seasons 2007 and 2008. This finding indicated that genetic differences among cultivars as well as seasonal changes have a significant influence on fruit quality. It was evident from this study that not only the cultivar and agricultural season, but also the interaction between the cultivar and season had significant influences on fruit quality. The best preferred cultivar, regarding physical/chemical fruit quality attributes, was Nudosa, performing the best regarding fruit mass and pulp glucose. Messina performed the best regarding 0 Bx. Nudosa and Messina performed the best regarding pulp fructose content, while Blue Motto had the best acidity levels (pH and TA). Sensory analysis, used to determine whether the consumer could distinguish among the available 33 cultivars was done by using the FCP technique and it was clear that the consumers could only successfully distinguish between the two seasons (77.72 %) , but not among the 33 different cactus pear cultivars. The fodder cultivar, Robusta, was an exemption and could be clearly distinguished from the other 32 cultivars. The sensory quality of cactus pear fruit obtained from the consumers was indeed influenced by the physical/chemical parameters. Cultivars like Robusta, Fresno and Nudosa had been significantly influenced by seasonal differences. The physical/chemical data and the sensory attributes were correlated.

Die kweek van turksvye is eenvoudig en dit kan in droer areas van Suid-Afrika geplant word, waar dit kan dien as veevoer. Turksvye is 'n bekostigbare, voedsame voedselbron vir laer-inkomste groepe. Glukose, as die primere suiker, saam met fruktose, wat dien as die sekondere suiker, gee aan turksvye 'n kenmerkende soet smaak. Suikerwaarde varieer van 10 tot 17 °Brix. Die pulp het 'n hoe pH waarde (> 4.5) en 'n lae suurheidsgraad (0.03- 0.12 %). Die doel van die studie was om die vrugkwaliteit van turksvye te bepaal. Fisies/chemiese en sensoriese kwaliteit was ge-Ewalueer vir seisoene 2007 en 2008. Daar was ook bepaal wat die omgewingsinvloede, naamlik reenval en temperatuur, op truksvye het. Sensoriese analise was toegepas deur die tegniek, "Free Choice Profiling", om te bepaal of die verbruiker tussen die smaak van 33 verskillende kultivars kon onderskei en sodoende ook die kultivar te identifiseer wat die meeste stabiel was in veranderde omgewingstoestande. Afleidend was daar bepaal of sensoriese kwaliteit van truksvye deur die fisies/chemiese eienskappe van die truksvy beinvloed deur die analise van fisies/chemiese data met die sensoriese resultate te korreleer. Daar was betekenisvolle verskille (p < 0.001) tussen die 33 kultivars in SuidAfrika in terme van fisies/chemiese samestellling vir seisoene 2007 en 2008. Hierdie bevinding toon dat truksvye geneties verskil en dat seisoensverandering 'n merkwaardige invloed op vrugkwaliteit het. Die studie het getoon dat vrugkwaliteit nie net deur die kultivar en seisoen beinvloed word nie, maar ook deur die interaksie tussen die kultivar en die seisoen. Die beste kultivar, ten opsigte van chemiese vrugkwaliteits-kenmerke, was Nudosa, wat die beste vertoon het betreffende vrugtemassa, pulp glukose. Messina het die beste gevaar ten opsigte van °Brix. Nudosa en Messina het die beste gevaar ten opsigte van pulp fruktose, terwyl Blue Motto die beste suurheidsvlakke gehad het (pH en TA). Sensoriese analise het getoon dat die verbruiker in staat was om tussen die 33 kultivars van 2007 en 2008 te kon onderskei, rnaar nie tussen die 33 afsonderlike kultivars nie. Robusta, wat as veevoer gebruik word, was 'n uitsondering en kon afsondelik van die 32 ander kultivars onderskei word. Sensoriese kwaliteit van truksvye word betekenisvol beinvloed deur die fisies/chemiese eienskappe van die truksvy. Kultivars soos Robusta, Fresno en Nudosa was betekenisvol beinvloed deur seisoimsverandering. Daar was 'n korrelasie tussen die fisies/chemiese kenmerke en sensoriese resultate.
Dissertation (M.Sc. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2010
Keywords: Cactus pear; Physical/chemical parameter; Sensory analysis; Fruit mass; Pulp percentage; Pulp pH; Total soluble solids; Titratable acid; Glucose; Fructose; Opuntia; Prickly pears -- Quality -- South Africa; Glucose; Fructose